Konsepsi Pendidikan Islam Terhadap Kekerasan Kepada Anak - Julianne Kamelia Riza; Rika Maidefvi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
The purpose of this study is to describe violence against children (Child Abuse) in the perspective of Islamic education. The method used in this research is library research (library research). By going through a developmental psychological approach used to analyze the concept of violence committed against children (Child Abuse). As well as a normative approach, which is seen in terms of religious values ??based on the Qur'an and Hadith. In analyzing the data using analytical descriptive method. The results of this study are (1) Deliberate actions that cause harm or harm to children physically or emotionally. (2) The influence of violence against children in the psychological development of children, namely children who experience abuse often show withdrawal, fear, or maybe aggressive behavior, unstable emotions. (3) Violence against children in the perspective of Islamic education In the context of education and teaching efforts. Islam allows doing physical actions as ta'dib (actions to educate) against children (educating, ie so as not to get used to doing intentional violations). Punishment means a form of loss or pain inflicted on someone who makes a mistake. The short-term goal of imposing the punishment is to stop the wrong behavior. The long-term goal is to teach and encourage children to stop their own misbehavior, so that children can direct themselves